Linking service quality to academic achievement: student perspectives from a Zimbabwean public university - Phillip Dangaiso; Maria Tsvere (Cogent Education, 2025)
Studies examining how universities could leverage service quality to enhance student academic achievement are largely scarce. Informed by the HEdPERF and HEDQUAL models, this study explored student perceptions of university service quality and academic achievement. Using purposive sampling, 11 student participants from a Zimbabwean public university were interviewed to respond to the research questions. Data were collected through face-to-face semi-structured interviews. Thematic analysis was employed to identify the educational quality dimensions that were aligned with academic success. These were academic aspects, support services, access-related quality and library services. In addition, the sub-themes that emerged from each of these themes were discussed. The study also revealed service quality gaps undermining student learning experiences and academic outcomes. These were inadequate faculty support, learning infrastructure gaps and limited access to subscription-based electronic library resources. To enhance student achievement, Zimbabwean public universities should adequately resource and reward academic faculty as well as subscribing on premium electronic library resources. In addition, universities should invest further in modern learning infrastructure and enhancing ease of contact between students and academic staff. This study provides practical contributions to university administrators, educators and policymakers seeking to bridge service quality gaps and augment student academic achievement.